Gastrointestinal Endoscopy In The Cat: Equipment, techniques and normal findings. Issue 11 (November 2013) - Stengel, Christiane; Robertson, Elise; Neiger, Reto
Practical relevance: Feline gastrointestinal (GI) endoscopy is in high demand, particularly by cat owners already aware of the clinical benefits and availability of this procedure within the human healthcare system. This article will provide a basic introduction to GI flexible endoscopy, covering important aspects of endoscope selection, clinical indications, and basic techniques required to perform a thorough and diagnostically meaningful examination in the cat. Clinical challenges: Challenges associated with implementing endoscopy in GI tract investigations can include lack of appropriate/suitable-sized equipment to perform a thorough examination in the cat, insufficient operator training/understanding in how to 'drive the scope' through the GI tract, and/or lack of confidence in differentiating normal from abnormal. Audience: This article is intended to familiarize and motivate the feline practitioner to develop basic endoscopic skills. Clinical proficiency can only be obtained through use of appropriate equipment, formal training and hours of practice indistinguishing normal from abnormal. Evidence base: The guidance contained in this article is based on a combination of the published literature, the authors' personal experience and the experience of colleagues.